Acetyl-Coenzyme A Can Regulate Activity of the Mitochondrial Pyruvate Dehydrogenase Complex in Situ - Budde, Raymond J. A. (1991)
In vitro, the pyruvate dehydrogenase complex is sensitive to product inhibition by NADH and acetyl-coenzyme A (CoA). Based upon K(m) and K(i) relationships, it was suggested that NADH can play a primary role in control of pyruvate dehydrogenase complex activity in vivo (JA Miernyk, DD Randall [1987] Plant Physiol 83:306-310). We have now extended the in vitro studies of product inhibition by assaying pyruvate dehydrogenase complex activity in situ, using purified intact mitochondria from green pea (Pisum sativum) seedlings. In situ activity of the pyruvate dehydrogenase complex is inhibited when mitochondria are incubated with malonate. In some instances, isolated mitochondria show an apparent lack of coupling during pyruvate oxidation. The inhibition by malonate, and the apparent lack of coupling, can both be explained by an accumulation of acetyl-CoA. Inhibition could be alleviated by addition of oxalacetate, high levels of malate, or l-carnitine. The CoA pool in nonrespiring mitochondria was approximately 150 micromolar, but doubled during pyruvate oxidation, when 60 to 95% of the total was in the form of acetyl-CoA. Our results indicate that in situ activity of the mitochondrial pyruvate dehydrogenase complex can be controlled in part by acetyl-CoA product inhibition.